There's a hummingbird in my backyard - Bogue, Gary (Heyday Books, 2010)
In their own backyard, the Baker family observes a pair of hummingbirds from their courtship dance through the day the fledglings are ready to leave the nest and return on their own. Includes facts about hummingbirds, and related websites and books.